The Widening Income Dispersion in Hong Kong: 1986-2006 - Lui, Hon-Kwong (Journal of Income Distribution®, 2011)
This article analyzes the changes in income dispersion in Hong Kong during the period 1986-2006. The decile ratios indicate that while the income dispersion of the upper income class has widened substantially, the income dispersion of the lower income class has narrowed. Although changing industrial composition has been named as the prime suspect that caused rising income inequality, it actually helped in reducing the earnings variance slightly. Moreover, 40 per cent of the overall increase in earnings variance is due to an employment shift from low-inequality to high-inequality occupations. The increase in the supply of post-secondary and associate-degree graduates was more than offset by an increase in the demand for better educated workers. As a result, the earnings premium for more better educated workers experienced a decline.